PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VIII - Melinda, Yohana (Jurnal Edukasi dan Penelitian Matematika, 2023)
One of the goals of learning mathematics is to understand mathematics concepts.. However in practice the Grade 8 students of SMPN 6 Sawahlunto still have very little understanding of mathematical concepts. One of the efforts to improve understanding of mathematical concepts is to implement a team assisted individualization cooperative learning model. The purpose of this study was to find out whether students in class VIII SMPN 6 Sawahlunto who learned through direct instruction have a better understanding of mathematical concepts than students who learned through team assisted individualization models. This type of study is quasi-experimental and uses a non-equivalent post-test-only control group design. Learning tools are tests for understanding mathematical concepts. A t-test is used to test hypotheses. Based on the data analysis it was found that the students had a better understanding of the mathematical concepts taught in the team-assisted individually collaborative learning model compared to the students under the direct instruction.  Keywords– Cooperative Learning, Direct Learning, Mathematical Concepts Understanding, Team Assisted Individualization.